Determinants and Academic Performance: The Role of Prerequisites in University Achievement - Maria Giulia Ballatore; Anita Tabacco (Excellence and Innovation in Learning and Teaching)
This study examines the relationship between incoming preparation and academic performance of engineering freshmen at Politecnico di Torino, within the context of transformative and sustainable processes in higher education. Based on a sample of 3,739 students, the research evaluates the predictive validity of the entrance exam (Test In Laib - TIL) and the national state exam (Esame di Stato – EdS), considering variables such as gender, geographical origin, and scholastic background. The results show a significant correlation between TIL scores and the university credits earned in the first year, highlighting the importance of the TIL in predicting academic success, while EdS scores are not correlated with performance. Students from scientific high schools and regions outside the North-West obtain higher TIL scores, indicating disparities in preparation. Gender differences also emerge: males achieve slightly higher TIL scores, while females score higher on the EdS. Binary logistic and quantile regression analyses confirm the effectiveness of the TIL as a predictive tool, suggesting the need to revise orientation and admission policies to better support students’ transition from school to university. These results are crucial for refining educational strategies, better aligning students’ preparation with academic and professional demands, contributing to reducing dropout rates and improving academic success.